Секретная просьба: повести и рассказы - Алексеев Сергей Петрович (1983)
Экземпляры: КХ (20120316) / Инвентарный номер: 804080 / Цена: 1.50 / Сис.шифр: Р2 / Авт.знак: А 47 / ГРНТИ: 17 / ББК: 84(2=411.2)6-4